Obtaining, characterizing and applying a Composite with Polyester Resin and Carnauba Leaf Petioles Powder (Research, Society and Development, 2020)
The carnauba, the tree of life, is a palm tree found in all regions of Brazil and has many applications, from electronics to cosmetics, with a greater emphasis on wax. The objective of this research was to obtain composites using petioles fibers from carnauba leaves and polyester resin. The powder was obtained using forage grinding and subsequent sieving, generating residues with different grain sizes. All the obtained granulometries were tested and the smaller one was chosen, due to its greater viability to obtain the composite, due to its better processability. Three mass proportions of the mixture between matrix and residues were chosen, 5%, 7.5% and 10%, since above that percentage there was a compromise in the processability and obtaining the composite studied. Mechanical, thermal and environmental characterizations were performed, which demonstrated the feasibility of the proposed composite. The carnauba powder was present in the composite as fill charge. The best formulation, 10%, was chosen to make a parabola of a solar cooker at concentration to produce cooking food. The composite can also be used in the manufacture of decorative panels for the support of televisions, as well as in the manufacture of furniture.